(E)-N-Benzylideneadamantan-1-amine - Jin, Xu-Dong (International Union of Crystallography, 2012)
In the title compound, C(17)H(21)N, the dihedral angle between the benzene ring and the imine group (—N=) is 5.1 (4)°. In the adamantane group, the C—C—C bond angles range from 107.88 (19) to 111.33 (17)°. Only weak van der Waals interactions contribute to the contribute to the packing of the molecules in the crystal..